2014
DOI: 10.1097/jom.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead, Manganese, and Aluminum Levels in a Regional Italian Cohort of ALS Patients

Abstract: Results confirmed the association between high Pb blood levels and ALS; on the contrary, Al and Mn did not differ significantly in patients and controls, suggesting that Mn and especially Al may play a less important role in the ALS pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…One study found that, compared to controls, Mn levels were elevated in serum but not CSF of ALS patients (Kapaki et al, 1997), while another found the reverse – an elevation among patients compared to controls in CSF but not plasma (Roos et al, 2013). Another study found no difference in Mn levels in serum of ALS patients and controls (Garzillo et al, 2014). One study reported an inverse association of ALS with Mn levels in blood cells (Nagata et al, 1985), while others found null associations in several blood compartments (Pamphlett et al, 2001) and in toenails (Bergomi et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…One study found that, compared to controls, Mn levels were elevated in serum but not CSF of ALS patients (Kapaki et al, 1997), while another found the reverse – an elevation among patients compared to controls in CSF but not plasma (Roos et al, 2013). Another study found no difference in Mn levels in serum of ALS patients and controls (Garzillo et al, 2014). One study reported an inverse association of ALS with Mn levels in blood cells (Nagata et al, 1985), while others found null associations in several blood compartments (Pamphlett et al, 2001) and in toenails (Bergomi et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies comparing trace metal levels in ALS patients and controls have reported inconsistent results, possibly because of variations in study design and small size, with 17 to 40 patients and 9 to 40 controls in each study (Bergomi et al, 2002; Garzillo et al, 2014; Kapaki et al, 1997; Nagata et al, 1985; Pamphlett et al, 2001; Roos et al, 2013; Supplemental Table 1). These studies measured metals in various biological samples, including cerebrospinal fluid (CSF), whole blood, blood cells, serum or plasma, and toenails.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In comparison, there is a study of the levels of lead in the blood of patients with ALS in an Italian agricultural area [104]. This study was not included in our meta-analysis since data on exposure were missing.…”
Section: Discussionmentioning
confidence: 99%
“…Also for aluminum, it was initially assumed a role in Amyotrophic Lateral Sclerosis, but has not been confirmed in more recent studies (44). Studies about other metals, including selenium (Se), zinc (Zn), copper (Cu) and manganese (Mn), have predominantly evaluated by high exposures toxic effects (45)(46)(47). Kapaki et al (48) found in Amyotrophic Lateral Sclerosis patients a significant reduction of copper in serum and CSF levels compared to the control group (20.25 ± 7.09 vs 30.86 ± 16.02 SD micrograms/l, and 913.21 ± 165.55 against 1020.17 ± 197.76 micrograms/l), and an increase in serum levels of manganese (3.59 ± 0.89 SD micrograms/l vs 3:03 ± 1:23 SD micrograms/l) supposing an imbalance in the homeostasis of essential trace elements in ALS patients.…”
Section: Introductionmentioning
confidence: 99%